Porosity Switching in Polymorphic Porous Organic Cages with Exceptional Chemical Stability. (25th February 2019) - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul
Abstract: Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host–guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution‐state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine‐linked (4+6) porous organic cage (TpOMe‐CDA ) is reported using 2, 4, 6‐trimethoxy‐1, 3, 5‐triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the ‐OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the ‐OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe‐CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12 m NaOH. Interestingly, TpOMe‐CDA exists in three different porous and non‐porous polymorphic forms (α, β, and γ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe‐CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus. Abstract : Poröser Polymorph : Verschiedene polymorphe Formen eines außergewöhnlich stabilen, Imin‐verbrückten, porösen organischen Käfigs, TpOMe‐CDA, wurden untersucht. Bemerkenswert sind die reversible Umschaltung der Porosität sowie die morphologische Diversität bei einer Exposition mit N, N ‐Dimethylformamid (DMF) und Chloroform.